Antimicrobial resistance and genetic characterization of Campylobacter spp. from three countries - Wieczorek, K.; Dykes, Gary; Osek, J.; Duffy, L. (2013)
The objective of this study was to determine the diversity among Campylobacter isolates from Australia (n = 20), Poland (n = 22), and Malaysia (n = 16) with respect to antimicrobial resistance (AMR), the presence of 8 putative virulence markers, flaA-RFLP and flaA-SVR, and a PCR binary typing system (P-BIT). AMR to nine antimicrobials was assessed using the Sensititre®Campylobacter plate. Only two (10%) Australian isolates were resistant, one to tetracycline and one to nalidixic acid. Polish isolates (12; 54.5%) carried multiresistance with the most common pattern (9 strains; 40.9%) ciprofloxacin, nalidixic acid, and tetracycline. All Malaysian strains were resistant to at least three antimicrobials, with 9 isolates carrying multiresistance to 8 antimicrobials. Distribution of the 8 virulence markers tested in this study varied between countries. Differences were noted between countries in the carriage of ciaB and the cdt gene cluster, responsible for invasion and toxin production, respectively. Typing of Campylobacter isolates using the P-BIT, flaA-SVR, and flaA-RFLP approaches revealed 50, 30, and 11 genotypes, respectively. A limited number of overlapping Campylobacter genotypes from different countries irrespective of the typing method used was observed. The combined molecular differentiation strategy gave insight into strain relationships both within and across countries. The resistance patterns identified in the study may lead to a better understanding of antibiotic resistance distribution among Campylobacter in geographically distant countries with different antimicrobial treatment policy.